Preoperative Lumbar Drain Use During Acoustic Neuroma Surgery and Effect on CSF Leak Incidence. (January 2016) - Crowson, Matthew G.; Cunningham, Calhoun D.; Moses, Helen; Zomorodi, Ali R.; Kaylie, David M.
Objective: To determine if preoperative lumbar drain (LD) use reduces the incidence of postoperative cerebrospinal fluid (CSF) leak in patients undergoing acoustic neuroma resection. Methods: Retrospective review of 282 patients presenting for acoustic neuroma resection between 2005 and 2014. Results: Two hundred and eighty-two patients had a mean tumor size of 19.1 mm ± 10.2 mm. Twenty-nine (10.3%) patients developed a postoperative CSF leak. Two hundred and twenty patients (78.0%) received a preoperative LD, and 20 (9.1%) developed a CSF leak. Sixty-two (22.0%) patients did not receive a preoperative LD, and 9 (14.5%) developed a CSF leak. No significant difference in CSF leak frequency was observed with use versus no use of a LD ( P = .23). Fifteen (5.3%) patients with an LD placed had a complication related to the LD. No significant difference in CSF leak frequency was observed with patient age, neurofibromatosis type-2 diagnosis, tumor size, or sidedness. Conclusions: Postoperative CSF leaks are among the most common complications of acoustic neuroma microsurgery. No formal guidelines exist for elective placement of a preoperative LD to lower the incidence of CSF leaks. Our reported CSF leak incidence with preoperative LD placement is not significantly lower than without LD use, and there is a complication rate associated with LD use.